2017
DOI: 10.1111/jfpp.13221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of orange juice authenticity in respect of added food flavors using dilution index

Abstract: Gas chromatography–mass spectrometry (GC–MS) study results, and dilution method results were compared in respect of food flavors in orange juices, which are sold in Ukrainian markets as “natural.” It was shown that the presence of d‐limonene, and benzoic acid, in commercial/industrial orange juices indicates the presence of added food flavors. New scientific evidence demonstrates the correlation between intensity of odor, represented numerically by dilution index (p < 0.05), and GC–MS results. It was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Moreover, a higher content of total ketones and total alcohols was detected in the commercially processed orange juice compared to freshly prepared homemade orange juice. The study by Bocharova et al [21] reported the detection of synthetic food flavor additives in commercial orange juice by identifying high concentrations of benzoic acid and D-limonene, which were absent in the freshly squeezed juice and the one prepared without the additives. Rothwell et al [22] reviewed the recently reported literature on VOC biomarker analysis in coffee, tea, and other non-fruit sweetened beverages.…”
Section: Voc-based Parametersmentioning
confidence: 99%
“…Moreover, a higher content of total ketones and total alcohols was detected in the commercially processed orange juice compared to freshly prepared homemade orange juice. The study by Bocharova et al [21] reported the detection of synthetic food flavor additives in commercial orange juice by identifying high concentrations of benzoic acid and D-limonene, which were absent in the freshly squeezed juice and the one prepared without the additives. Rothwell et al [22] reviewed the recently reported literature on VOC biomarker analysis in coffee, tea, and other non-fruit sweetened beverages.…”
Section: Voc-based Parametersmentioning
confidence: 99%
“…Orange juice is the most popular fruit juice, representing 50% of worldwide consumption, and its authentication and quality assurance represents a very important issue for consumers. Different methodologies have been reported using GC-MS to evaluate orange juice quality, some of them connecting the volatile profile of orange juices with flavor and aroma [37,95,96]. In this context, a new flavor index was proposed by Schmutzer et al calculated as the total sesquiterpenes of a juice sample divided to total terpenes (without limonene).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…A threshold value of a minimum of 40% is proposed to categorize orange juices from concentrate as high or lower value [37]. The presence of benzoic acid and D-limonene in orange juice reveals food flavors addition [95] while total alcohols and total ketones can be used to differentiate freshly squeezed orange juices with commercial orange juices and orange nectars, as the high concentrations of alcohols and ketones is indicative of sample processing and thermal treatment [37]. Varietal discrimination of orange juices was also achieved using their volatile profile in combination with new approaches based on Artificial Neural Networks (ANN) and Genetic Algorithms (GA).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Therefore, it is crucial to monitor and control the usage of benzyl alcohol. The general determination methods are gas chromatography (GC) [3] and high performance liquid chromatography (HPLC), [4] but they suffer from high‐cost equipment and complicated operational procedures. Enzymatic catalysis [5] possesses the advantages of high efficiency and excellent specificity.…”
Section: Introductionmentioning
confidence: 99%